Molecular Imaging of Therapeutic Potential of Reporter Probes - Thakur, Bhushan; Chatterjee, Subhoshree; Chaudhury, Smrita; Ray, Pritha (Current Drug Targets, 2015)
Success of medical treatments for any pathological disorders majorly depends on the efficacy of the therapeutic molecules and their delivery to the target sites. Non-invasive molecular imaging technologies have emerged as prime methods for validating both these aspects ranging from preclinical level to clinical application. Reporter genes and the respective reporter probes are essential components of molecular functional imaging that gained wide popularity throughout the world due to easy adaptation, user friendly software and cost-effective experiments. However, to monitor the therapeutic effects, reporter gene-reporter probes (RG-RP) are often combined with separate introductions of therapeutics whose delivery at target sites are not appropriately measured. A small group of reporter genes is associated with probes that behave like a signature as well as a therapeutic molecule thereby having theranostic properties. This Reporter Gene-Therapeutic Reporter Probe (RG-TRP) system bears additional advantages over RG-RP system and holds the promise of direct translational applications in humans. This short review focuses on describing the currently available and validated RG-TRP systems, delivery vehicles, associated imaging modalities, applications in various pathological conditions along with the merits and demerits. Identification of new RG-TRP system will open new direction in theranostic imaging with potential human applications.
Keywords: reporter probe